The influence of virgin red palm oil on the physical and textural properties of various vegetable full-fat mayonnaise - Wiguna, Bangkit; Aji, Galih Kusuma; Rachman, Dicki; Nasori, Achmad Sofian; Muhamaludin,; Maryana, Erma; Atmaji, Priyo; Taniwiryono, Darmono; Purwanto, Wahyu; Susetyo, Indra Budi; Kahfi, Jordan (Penerbit Universiti Kebangsaan Malaysia, 2023)
Mayonnaise is a type of semi-solid oil in water emulsion containing vegetable oil as the oil phase and egg yolk (emulsifier), vinegar, salt, sugar, and spices (especially mustard) as the water phase. In this study, full-fat mayonnaise is based on various vegetable oils (sunflower oil, sesame oil, and coconut oil). Virgin red palm oil (VRPO), substituting sunflower oil, sesame oil, and coconut oil, was added to the mayonnaise formula as a 0%, 5%, 10%, and 15% bioactive component. The physical properties of the full-fat mayonnaise were investigated by measuring viscosity, pH value, color, and emulsion stability or creaming index. Textural properties including firmness, consistency, and cohesiveness were evaluated using a texture analyzer. This study aimed to identify the effect of adding VRPO to the mayonnaise formula on the physical and textural properties of the vegetable full-fat mayonnaise sample. The result of this study found that the pH value of added VRPO (5, 10, and 15%) in all mayonnaise samples was higher considerably (p<0.05) compared to the mayonnaise without VRPO addition. Moreover, the color of mayonnaise from different vegetable oils when supplemented with VRPO was significantly decreased (p<0.05) in the L* values, indicating a reduction in the lightness. Conversely, there was a significant increase (p<0.05) in the a* values, showing an increase in redness, and b* values that demonstrated an increase in yellowness, in all of the mayonnaise samples when added with the VRPO. This study also highlighted that there was a significant difference (p<0.05) in the texture between all mayonnaise samples, showing that supplemented VRPO in vegetable oils was giving a lower value of firmness and consistency and a higher value of viscosity index. In conclusion, the addition of VRPO increases the physical characteristics such as pH, color (redness and yellowness), and creaming index, as well as reduces the textural features (firmness, and consistency) in full-fat mayonnaise.